ANALISIS KERJASAMA TRIPUSAT PENDIDIKAN SEBAGAI UPAYA PENINGKATAN MUTU PENDIDIKAN AGAMA ISLAM (STUDI KASUS DI SMA NEGERI 2 KOLAKA) - Maulininsyah Maulininsyah (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
In developing basic science and technology abilities and skills, the teaching materials used refer to the Islamic Religious Education learning strategy. As Islamic Religious Education or PAI is basically a normative effort to help a person or group of students in developing a way of life (how to live and take advantage of life and life in accordance with Islamic teachings and values), Islamic life attitudes, which are manifested in everyday life skills.First, the formulation of the problem in this study, what types of learning strategies are used by teachers at SDIT Al-Farabi Pomalaa. Second, what are the supporting and inhibiting factors in implementing the learning strategies of Islamic religious education teachers at SDIT Al-Farabi Pomalaa. The research objectives were to determine the Application of Learning Strategies for Islamic Religious Education Teachers at SDIT Al-Farabi Pomalaa and to determine the supporting and inhibiting factors in implementing Islamic religious education teacher learning strategies.The research method used is a qualitative approach with descriptive type. The data is collected by conducting observations, interviews and documentation, then analyzed inductively.Based on the results of this study, the types of learning strategies used by Islamic Religious Education teachers were direct learning strategies and indirect learning strategies. Because students prefer to receive material with audio visual or film screenings related to material taken from auidio visual shows. Supporting factors, namely the school environment is a bit far from the crowd and noise such as the sound of vehicles on the main road, a safe school atmosphere and the school environment is always controlled, there is cooperation with the parents of students, and the surrounding community. The inhibiting factor is the lack of facilities needed by a teacher, students are still less active.